2014
DOI: 10.1590/0102-311x00017113
|View full text |Cite
|
Sign up to set email alerts
|

Equidade no acesso ao rastreamento mamográfico do câncer de mama com intervenção de mamógrafo móvel no sul do Rio Grande do Sul, Brasil

Abstract: Equidade no acesso ao rastreamento mamográfico do câncer de mama com intervenção de mamógrafo móvel no sul do Rio Grande do Sul, Brasil Equity in access to breast cancer screening in a mobile mammography program in southern Rio Grande do Sul State, BrazilEquidad en el acceso a la detección por mamografía del cáncer de mama con el uso del mamógrafo móvil en el sur del Rio Grande do Sul, Brasil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 17 publications
(17 reference statements)
1
11
0
15
Order By: Relevance
“…In contrast, in the public institution, women had an average age similar to the national of around 50 years. (7,8) The explanation for this condition can be that younger women at reproductive ages are more likely to seek medical service, therefore are more examined, which can provide an early diagnosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the public institution, women had an average age similar to the national of around 50 years. (7,8) The explanation for this condition can be that younger women at reproductive ages are more likely to seek medical service, therefore are more examined, which can provide an early diagnosis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Results show the occurrence of breast cancer within an age group younger than the national average (50 years old), fact which was considered little frequent in the literature (5 to 7% of the cases) (Nunes, Silva, Ribeiro, Campelo & Veras, 2013; Instituto Nacional do Câncer [INCA], 2014;Renck et al, 2014). Younger women of reproductive age go more often to the doctor and are more frequently examined, which contributes to early diagnosis (Lima et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…There is a better adherence of this exam among individuals with high family income, good schooling and residing in the urban zone, 17 a characteristic that was found very diversified among the women interviewed, finding different degrees of schooling.…”
Section: Methodsmentioning
confidence: 90%
“…When asked if they arrived at the Breast / IMIP Center with the referral form / SISCAN, 80.7% (71) stated that they were in possession of such referral; 19.3% (17) of the interviewees explained that they were not in possession of this document, a very significant number, even more when it was observed that of those 19.3% (17) who arrived without referral, all were able to perform mammography.…”
Section: Methodsmentioning
confidence: 99%